2012
DOI: 10.1007/s10165-012-0800-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and correlation with disease-specific variables, spinal mobility measures, and health-related quality of life in ankylosing spondylitis

Abstract: Patients with AS defined significantly more fatigue when compared with healthy persons. MAF was related to clinical and functional status and HR-QoL of patients with AS. We assume that MAF can be used as a sensitive fatigue measure in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that patients with ax-SpA report HRQOL scores that are similar to those reported for other inflammatory diseases [2,10], but lower than those in healthy controls [1,4,[11][12][13]. Women with the ax-SpA report lower HRQOL than men [14][15][16], and decreased HRQOL in patients with ax-SpA is associated with fatigue [17], increased disease activity, decreased daily activity and exercise [4,[18][19][20], pain, and adverse psychological factors such as body-image disturbance, anxiety and depression [21,22]. In the new millennium, effective new treatments have become available for Ax-SpA [e.g.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies have shown that patients with ax-SpA report HRQOL scores that are similar to those reported for other inflammatory diseases [2,10], but lower than those in healthy controls [1,4,[11][12][13]. Women with the ax-SpA report lower HRQOL than men [14][15][16], and decreased HRQOL in patients with ax-SpA is associated with fatigue [17], increased disease activity, decreased daily activity and exercise [4,[18][19][20], pain, and adverse psychological factors such as body-image disturbance, anxiety and depression [21,22]. In the new millennium, effective new treatments have become available for Ax-SpA [e.g.…”
mentioning
confidence: 68%
“…Multivariable linear regression analysis, backward procedure (p = 0.20), was used to examine the demographic and disease-related variables at baseline that were associated with changes in HRQOL (delta SF-6D, 15D, SF-36 PCS and SF-36 MCS scores). The independent variables in the multiple analyses were chosen based on univariate associations with one of the delta HRQOL values (p < 0.10), clinical experience and factors found to be associated with HRQOL in previous studies [17,22,39]. These factors also resonate with the wider theory within the field [24,40].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Multiple linear regression analysis (general linear model (GLM) in SPSS) was used to examine the adjusted association between demographic- and disease-related variables and HRQoL (SF-36-PCS, SF-36-MCS, 15D and SF-6D scores). The independent variables in the multiple analyses were chosen based on univariate associations with HRQoL, clinical experience and factors associated with HRQoL in previous studies [ 6 , 15 , 37 ]. In the final multivariate model, we included the demographic variables, disease activity (assessed by BASDAI and MASES scores), health status (assessed by HAQ, BASFI and BAS-G scores), damage (assessed by BASMI score), co-morbidity and treatment centre as independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…However, patients with ax-SpA report lower HRQoL than do healthy controls [ 3 , 12 ], and women with the disease report a lower HRQoL than do men [ 2 , 13 , 14 ]. Decreased HRQoL in patients with ax-SpA is associated with fatigue [ 15 ], increased disease activity, decreased daily activity and exercise [ 16 – 18 ], pain, and adverse psychological factors such as body image disturbance, anxiety and depression [ 6 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn will result in loss of work productivity and increased socioeconomic burden (2,3). Studies have also shown that patients with axial SpA report a lower HRQoL than do healthy controls and this reduction in HRQoL is associated with fatigue, pain, increased disease activity, and decreased daily activity and exercise (7)(8)(9). In addition, a lower HRQoL in SpA patients is associated with adverse psychological outcomes and a higher prevalence of anxiety and depression (10,11).…”
Section: Introductionmentioning
confidence: 99%